2003
DOI: 10.5194/hess-7-283-2003
|View full text |Cite
|
Sign up to set email alerts
|

Review of recent advances in index flood estimation

Abstract: Index flood estimation for regional flood frequency analysis needs to be based on the information available. The most appropriate method depends on the specific application and its choice requires a problem-oriented analysis. This paper presents a simple theoretical framework to deal with index flood estimation for a specific river site. The methodological approaches available for the purpose are reviewed. For each, the information required is specified and the reliability of the estimate, particularly desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 22 publications
0
63
0
2
Order By: Relevance
“…Other conceptual approaches have been also proposed, based on an analytical derivation of the probability distribution of floods (e.g. Becciu et al, 1993;Brath et al, 2001;Bocchiola et al, 2003). The index flood estimation method based on the rational formula implicitly assumes that the average value of the annual maximum peak discharges is related to the average value of the annual maximum rainfall depth within a critical time interval, which is assumed equal to a characteristic time scale of the catchment response.…”
Section: F Preti Et Al: Forest Cover Influence On Regional Flood Frmentioning
confidence: 99%
“…Other conceptual approaches have been also proposed, based on an analytical derivation of the probability distribution of floods (e.g. Becciu et al, 1993;Brath et al, 2001;Bocchiola et al, 2003). The index flood estimation method based on the rational formula implicitly assumes that the average value of the annual maximum peak discharges is related to the average value of the annual maximum rainfall depth within a critical time interval, which is assumed equal to a characteristic time scale of the catchment response.…”
Section: F Preti Et Al: Forest Cover Influence On Regional Flood Frmentioning
confidence: 99%
“…divided by an index value (e.g. Bocchiola et al, 2003), have identical frequency distributions across all sites within a given homogenous area, or region (Hosking and Wallis, 1993;. The regional distribution is usually named growth curve and is more accurate as compared to single site analysis (e.g.…”
Section: T Imentioning
confidence: 99%
“…The index value can be calculated by the single site sample average (e.g. Bocchiola et al, 2003), or by the median (middle ranking value of the single site observed series, e.g. Robson and Reed, 1999) or by a site to site location parameter (e.g.…”
Section: Index Value Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…As CASC2D is an event model, initial conditions are also included in the criteria. The proposed procedure that will be used is a hydrologic simulation using monte -carlo (MC) methods (e.g., Bocchiola et al, 2003) coupled wi th the stochastic storm transposition (SST) technique (Foufoula -Georgiou, 1989) to estimate extreme rainfall probabilities. The procedure is based on the stochastic storm transposition and runoff approach used by Franchini et al (1996) with some modifications.…”
Section: Distributions For Process Parameters and Inputsmentioning
confidence: 99%